Respuesta :
The shortest way is to use the sum formula for GP
S =a(1-rⁿ) /(1-r)
a=6
r=(-4)
n=7 (seventh term) ===> S=6(1-(- 4)⁷)/[1- -4)] =19,662
S =a(1-rⁿ) /(1-r)
a=6
r=(-4)
n=7 (seventh term) ===> S=6(1-(- 4)⁷)/[1- -4)] =19,662
Answer:
Sum of the geometric sequence is 19662.
Step-by-step explanation:
Sum of the terms in a geometric series is represented by the formula
[tex]s_{n}=a\frac{(1-r^{n}) }{1-r}[/tex]
In this formula a = first term
r = common ratio
n = number of terms
Given in the question
a = 6
r = (-4)
n = 7
[tex]S_{7}=(6)\frac{[1-(-4)^{7}] }{[1-(-4)]}=6.\frac{(1+16384)}{(1+4)}=\frac{(6)(16385)}{5}= 19662[/tex]
Therefore sum of the sequence is 19662